Peningkatan Kemandirian Belajar Akuntansi Melalui Metode Problem Based Learning (PBL) Pada Siswa Kelas X B - Perbankan Syariah Semester Genap SMK Teknosa Surakarta Tahun Ajaran 2016/2017 - Setia Pratama, Febri; , Dr. Djalal Fuadi, M.M (2017)
This research is aimed to increase the independence of learning accounting through the metode of problem based learning (pbl) in class X B-Peranan Syariah SMK Teknosa Surakarta academic year 2016/2017. Type of this resesarch is classroom action research conducted in two cycles. Subject of the research is the teacher who give action and the recipient of the action is the students of X B-Perbankan Syariah class SMK Teknosa Surakarta totaling 25 students. The method collecting of data used interview, observation, field notes, and documentation. The technique for anaizyng data used reduction of data, presebtation of data, and verification. The result of this research showed an increased in independent learning accounting that can be seen from the indicators, namely: 1) Identify learning needs before the action as many as 8 students (32%) and the end of the action as many as 19 students (76%), 2) Formulate learning objectives prior to the action as many as 6 students (24%) and the end of the action as many as 18 students (72%), 3) Finding the source of study are required before the measure as many as 10 students (40%) and the end of the action as many as 23 students (92%), 4) Carry out independent assignment before the action 9 students (36%) and the end action 20 students (80%), 5) Evaluating the result of study before action 10 students (40%) and the end of the action as many as 21 students (84%). Thus concluded that the uses of method of problem based learning (pbl) can improve students' independence to learning of accounting for X B-Perbankan Syariah class of SMK Teknosa Surakarta academic year 2016/2107.